Toxicity and residual effects of azadirachta indica var. siamensis extract and cyhalothrin on Apis folrea and Apis cerana - Chuleemas Boonthai (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 1994